2017
DOI: 10.19082/5142
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between medication errors with job satisfaction and fatigue of nurses

Abstract: BackgroundMedication errors which can cause several medical malfunctions, have been in the spotlight recently. Job satisfaction and fatigue seems to be related to the increase of medication errors in nursing.ObjectiveThis study aimed to determine the correlation between the amount and type of medication errors with job satisfaction and fatigue of nurses working in Shahid Sadoughi hospital in Yazd-Iran.MethodsThis is a descriptive study by a cross-sectional and correlational approach conducted on all the nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Female nurses had higher intrinsic JS. Bolandianbafghi et al () found the same results, and according to Joolaee et al (), a negative attitude in male nurses may be the reason. This negative attitude may stem from society, nurses or other health professionals.…”
Section: Discussionmentioning
confidence: 63%
“…Female nurses had higher intrinsic JS. Bolandianbafghi et al () found the same results, and according to Joolaee et al (), a negative attitude in male nurses may be the reason. This negative attitude may stem from society, nurses or other health professionals.…”
Section: Discussionmentioning
confidence: 63%
“…Fatigue, feelings of weakness, and weariness of mind may interfere with one’s ability to remain focused at work and be successful in their role as a caregiver. 42 Because of these stressors, nurses were unable to concentrate on their work and had a lower QWL.…”
Section: Discussionmentioning
confidence: 99%
“…The job satisfaction of nurses is related to numerous important organizational outcomes (Saber, ), including organizational commitment (Ahmad & Oranye, ), turnover (Poghosyan et al., ) and quality patient care (Djukic, Kovner, Brewer, Fatehi, & Cline, ). In consideration of the currently low job satisfaction of nurses (Bolandianbafghi, Salimi, Rassouli, Faraji, & Sarebanhassanabadi, ; Liu et al., ; McGlynn, Griffin, Donahue, & Fitzpatrick, ), job satisfaction problems should be addressed.…”
Section: Introductionmentioning
confidence: 99%